Kentucky Probationers' and Parolees' Perceptions of the Severity of Prison versus County Jail and Probation - May, David C. (2004)
This study extends a growing body of research on offenders' perceptions of the punitiveness of criminal sanctions. Specifically, we examine punishment equivalency ratings by Kentucky probationers and parolees (N-588) meant to gauge their perceptions of the severity of prison compared to both probation and county jail. Ratings are analyzed by several demographic characteristics. We find that, in general, survey respondents pereceived county jail as more severe than prison but that probation was rated as less severe